Antimicrobial Activity of Skin Secretion of Rana hosii Frog (Anura: Ranidae) against several pathogenic microbes - Feskaharny Alamsjah; Djong Hon Tjong; Zil Fadhillah Rahma (Jurnal Biologi Universitas Andalas, 2020)
The research on antimicrobial activity of skin secretion derived from Rana hosii (Anura: Ranidae) against several pathogenic microbes had been conducted at Microbiology Laboratory and at Genetics and Biomolecular Laboratory, both in the Biology Department, Universitas Andalas. The research used to survey and experimental methods. The study aimed to determine the effectivity of Rana hosii skin secretion to inhibit microbial activity, hence it tested onto some pathogenic microbes such as Escherichia coli, Staphylococcus aureus and Candida albicans. The results showed that the biggest inhibition zone formed against E. coli was 10.96 + 0.63 mm, on S. aureus was 11.74 + 1.00 mm, while on C. albicans was 7.42 + 0.80 mm. The results indicated that the skin secretions from Rana hosii frog could be a potential broad-spectrum antibacterial, and antifungal activity against C. albicans.